Pengaruh Model Pembelajaran Self Organized Learning Environment (SOLE) Berbantuan Kahoot Terhadap Berpikir Kritis dan Kemandirian Belajar Peserta Didik Kelas XI - Dwi Kesumawardani, Aryani; Juabdin Sada, Heru; Putri, Alda (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study aims to determine the effect of the Self Organized LearningEnvironment model assisted by Kahoot on critical thinking and learningindependence of class XI students. This research is a quantitative research withthe method used, namely Quasy Experimental with a Pretest-Posttest Control Group research design. The sampling technique used in this study is Cluster Random Sampling. The population used in this study were all students of class XI MA Negeri 1 Pringsewu. The sample of this study consisted of two classes, namely the experimental class and the control class. The technique of collectingcritical thinking data in the form of Essay questions and Likert scale questionnaire sheets for Learning Independence. The research hypothesis test used Manovawith a significance level of α = 0.05. Based on the results of the study, it shows that the significant value is 0.000 < α = 0.05 with the provision that H₁ is accepted and H0 is rejected. The conclusion in this study is (1) there is an influence of the Self Organized Learning Environment model assisted by Kahoot on critical thinking of class students, (2) there is an influence of the Self Organized Learning Environment model assisted by Kahoot on learning independence of class XI students.